Effective Resource Allocation and Load Balancing in Hierarchical HetNets: Toward QoS-Aware Multi-Access Edge Computing. (29th October 2021) - Bonab, Mohammad Jalilvand Aghdam; Kandovan, Ramin Shaghaghi
Abstract: Mobile edge computing (MEC) is a key feature of next-generation heterogeneous networks aimed at providing a variety of services for different applications by performing related processing tasks closer to the user equipment. In this research, we investigated on connection management approaches in multi-access edge computing systems. This paper presents joint radio resource allocation and MEC optimization in a multi-layer NOMA HetNet in order to maximize system's energy efficiency. The continues carrier allocation and handoff decision variables, in addition to the interference incorporated in the goal function, modifies the primary optimization problem to a mixed integer nonlinear programming. Network selection is done statically based on the Analytic Hierarchy Process, and station selection is done dynamically based on the Data Envelope Analysis method. Also, an effective feedback mechanism has been designed in collaboration with the server resource manager to solve a global optimization problem in order to load balancing and meet the users quality of service constraints simultaneously. To reduce the computational complexity and to achieve a locally optimal solution, we applied variable relaxation and majorization minimization approach in which offloading decision and multi-part Markov noise analysis have been developed to model users' preferences without the need for explicit information from the users. Based on the simulations, the proposed approach not only results in a significant increase of system's energy efficiency but also enhances the system throughput in multiple-source scenarios.